Um estudo da relação entre os preços de Petróleo, Minério de Ferro, Superfosfato, Uréia e Potássio e o custo de produção da Commodity Café nas principais regiões produtoras do país - Ferreira, Luiz Gustavo (2011)
The variables of farm costs have important relationships with other economic variables and it is important for public and private agencies identifying such relationships to better plan the agricultural activity as a whole. In this context, this study aimed to investigate which relationship exists between the change in commodity prices Oil, Iron ore, Superphosphate, Urea and Potassium chloride and the production costs of commodity coffee using as a space of time the period 2003 -2011 and the physical regions that showed costs disclosed by CONAB. The methodology used was quantitative, with the cluster analysis, correlation coefficient of Pearson and canonical correlation coefficients. Cluster analysis showed that the cost Irrigation in BA is relevant. The Pearson correlation showed significant results, and the iron commodities, oil and potassium had significant correlations and the MG region showed more significant results. Finally, canonical correlation analysis indicated that there is an association between non-agricultural commodities Oil, Iron ore, Superphosphate, Urea and Potassium and some costs of commodity coffee. Thus, we see the importance of this study to help the understanding of the coffee culture and the need for further studies in order to deepen deepen knowledge in this area.